2010
DOI: 10.1089/scd.2009.0262
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Melastatin Type 7 Channel Is Critical for the Survival of Bone Marrow Derived Mesenchymal Stem Cells

Abstract: The transient receptor potential melastatin type 7 channel (TRPM7) is a member of the TRP family of ion channels that is essential for cell proliferation and viability. Mesenchymal stem cells (MSCs) from bone marrow are a potential source for tissue repair due to their ability to differentiate into specialized cells. However, the role of TRPM7 in stem cells is unknown. In this study, we characterized TRPM7 in mouse MSCs using molecular biology, immunocytochemistry, and patch clamp. We also investigated TRPM7 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 45 publications
3
53
0
4
Order By: Relevance
“…This gene is ubiquitously expressed and is greatest in heart, pituitary gland, bone, and adipose tissue (70,83). In the bone TRPM7 may be regulating extracellular calcium and magnesium, responding to ischemic reperfusion, or regulating osteogenesis (20,57,70). TRPM7 is also abundant in WAT, but the level of expression in bone marrow greatly exceeds that seen in adipocytes, so this is not likely due to the increase in adipocytes alone (35).…”
Section: Discussionmentioning
confidence: 99%
“…This gene is ubiquitously expressed and is greatest in heart, pituitary gland, bone, and adipose tissue (70,83). In the bone TRPM7 may be regulating extracellular calcium and magnesium, responding to ischemic reperfusion, or regulating osteogenesis (20,57,70). TRPM7 is also abundant in WAT, but the level of expression in bone marrow greatly exceeds that seen in adipocytes, so this is not likely due to the increase in adipocytes alone (35).…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of nonselective cation channels, TRPM7 channels are mostly permeable to divalent cations, such as Ca 2+ , Mg 2+ (Sahmoun and Singh, 2010;Monteilh-Zoller et al, 2003;Schmitz et al, 2003). It constitutively expresses on heart, liver, kidney, lung, brain and other organs and tissues of mammals, participates in many important physical processes such as cell proliferation (Abed and Moreau, 2007;Jiang et al, 2007), survival (Cheng et al, 2010;Wykes et al, 2007) (Clark et al, 2008;Tsavaler et al, 2001), adhesion (Clark et al, 2006;Su et al, 2006), embryonic development (Jin et al, 2012), regulating of Ca 2+ homeostasis (Holoch and Griffith, 2009), and the release of neurotransmitters (Oancea et al, 2006) of the cells. Ion channels are also concerned with several diseases in addition to these life supporting-activities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TRPM7 is also required for maintenance of bone marrow-derived mesenchymal stem cells (24). The question is why TRPM7 is dispensable for survival of most terminally differentiated cells types and some multipotent stem cells, such as NP cells, but is required for pluripotent stem cells and some multipotent stem cells, such as mesenchymal stem cells.…”
Section: −/−mentioning
confidence: 99%